1978
DOI: 10.1007/bf01937024
|View full text |Cite
|
Sign up to set email alerts
|

HLA BW54 and B5 in Japanese diabetics with juvenile-onset and insulin-dependency (with special reference to the family history)

Abstract: The frequency of HLA BW54 and B5 in Japanese patients with JOD is increased and decreased, respectively. In JOD patients without a family history of MOD, the frequency of BW54 is significantly increased, whereas in JOD patients with a positive family history the frequency was not increased in a statistically significant manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In Caucasians, its association with HLA-A1, -B8 and/or -B15 was first reported, and much more close relation with HLA-DR3 and/or -DR4 was found later, after the discovery of D-DR loci (Tiwari and Terasaki, 1985). In Japanese, HLA-Bw54, one of the specific antigen for Japanese, was found to be associated with IDDM Kawa et al, 1978). Later it was discovered that Japanese IDDM was also associated with DR3 and DR4 (Sakurami et al, 1982;Batchelor and Morris, 1977).…”
Section: Diseases Which Associate Different Antigens Between Japanesementioning
confidence: 98%
“…In Caucasians, its association with HLA-A1, -B8 and/or -B15 was first reported, and much more close relation with HLA-DR3 and/or -DR4 was found later, after the discovery of D-DR loci (Tiwari and Terasaki, 1985). In Japanese, HLA-Bw54, one of the specific antigen for Japanese, was found to be associated with IDDM Kawa et al, 1978). Later it was discovered that Japanese IDDM was also associated with DR3 and DR4 (Sakurami et al, 1982;Batchelor and Morris, 1977).…”
Section: Diseases Which Associate Different Antigens Between Japanesementioning
confidence: 98%
“…Studies of the HLA system in non-Caucasian populations have revealed an association between HLA-B8 and IDDM in Black Americans (Cahill 1979), but no association between either B8 or 815 and diabetes in Japanese. In contrast, in the latter group, diabetes has been associated with Bw54, a variant of Bw22 (Kawa et al 1977(Kawa et al , 1978, and with B12 (Nakao et al 1977). In addition, both groups of workers also reported a decreased incidence of B5 in their diabetics.…”
mentioning
confidence: 99%